The Emptied Kingdom- Decolonizing the Demographic Reconstruction of Kongo’s Depopulation2016 - Nsiangani, Kibavuidi (CEMA - USK, 2016)
The standard demographic reconstruction of the Kingdom of Kongo's depopulation under the Atlantic slave trade relies on a single, biased archive: European shipping records (e.g., the "1.8 million" captives in SlaveVoyages). This article rejects this Eurocentric data as a scientific total, instead treating it as a censored minimum. The core research question is: How large was the demographic shock experienced by Kongo, and why has a single colonial archive defined its limits? Our methodology uses Monte Carlo simulations to triangulate four sources: surviving trade records, Afonso I’s letters, oral histories and archaeology, and a probabilistic model including parameters for under-documentation and pre-embarkation mortality. The findings show the documented 1.8 million is a floor, not a total. Central estimates for total removals are typically 8–12 million, with upper bounds reaching 15–18 million. Proportional losses of the 1480 population cluster around 30–60%, aligning with Afonso I’s description of the kingdom "emptying." The conclusion is that the perception of collapse was a response to a real demographic catastrophe. Decolonial demographic reconstruction must abandon the illusion of precision from a single colonial archive and work with multi-source ranges. Keywords: Kingdom of Kongo; Atlantic slave trade; historical demography; decolonial methods; SlaveVoyages; Afonso I; Monte Carlo simulations; coloniality of power; oral tradition; archival bias.